2013
DOI: 10.1002/jgrd.50342
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation chemistry and ozone production: Results from SHARP 2009 in Houston, Texas

Abstract: [1] Ozone (O 3 ) and secondary fine particles come from the atmospheric oxidation chemistry that involves the hydroxyl radical (OH) and hydroperoxyl radical (HO 2 ), which are together called HO x . Radical precursors such as nitrous acid (HONO) and formaldehyde (HCHO) significantly affect the HO x budget in urban environments. These chemical processes connect surface anthropogenic and natural emissions to local and regional air pollution. Using the data collected during the Study of Houston Atmospheric Radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
119
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 82 publications
22
119
2
2
Order By: Relevance
“…Details will be presented in a thorough radical study prepared by Ren et al (2012). These results are similar to those of Chen et al (2010) and Mao et al (2010) for the same site in September 2006.…”
Section: Comparison Between Measured Calculated and Modeled P (O 3 )supporting
confidence: 60%
“…Details will be presented in a thorough radical study prepared by Ren et al (2012). These results are similar to those of Chen et al (2010) and Mao et al (2010) for the same site in September 2006.…”
Section: Comparison Between Measured Calculated and Modeled P (O 3 )supporting
confidence: 60%
“…In urban environments, measured HO 2 concentrations were sometimes found to agree with model predictions Emmerson et al, 2007; Published by Copernicus Publications on behalf of the European Geosciences Union. 96 M. M. Lew et al: Hydroperoxy radical in the atmosphere using laser-induced fluorescence 2009b; Michoud et al, 2012;Lu et al, 2013;Ren et al, 2013;Griffith et al, 2016), while other times the measurements were found to be both lower (George et al, 1999;Konrad et al, 2003) and higher than model predictions Ren et al, 2003;Emmerson et al, 2005;Kanaya et al, 2007a;Chen et al, 2010;Sheehy et al, 2010;Czader et al, 2013;Griffith et al, 2016). In forested environments, measured HO 2 concentrations were sometimes found to agree with model predictions (Tan et al, 2001;Ren et al, 2005Ren et al, , 2006 but were often found to be either lower (Carslaw et al, 2001;Kanaya et al, 2007bKanaya et al, , 2012Whalley et al, 2011;Mao et al, 2012;Griffith et al, 2013) or higher than model predictions (Carslaw et al, 2001;Kubistin et al, 2010;Kim et al, 2013;Hens et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…This difference between oceanic and continental free troposphere vanishes in the upper troposphere, where O 3 production prevails (Klonecki and Levy, 1997;. Studies that infer net ozone production at least in part from in situ measurements are rare and often limited to the boundary layer (Ren et al, 2013;Liu et al, 2012;Sommariva et al, 2011;Kleinman et al, 2005;Kanaya et al, 2002;Kleinman, 2000;Zanis et al, 2000;Penkett et al, 1997;Cantrell et al, 1996). A number of studies based on aircraft measurements have been performed, using in situ O 3 , CO, NO x , volatile organic compounds (VOCs) and radiation measurements in combination with a box model to calculate HO x and RO x radical levels to study NOPR in the free troposphere (Kuhn et al, 2010;Kondo et al, 2004;Davis et al, 2003;DiNunno et al, 2003;Ko et al, 2003;Reeves et al, 2002;Olson et al, 2001;Schultz et al, 1999;Crawford et al, 1997a, b;Davis et al, 1996;Jacob et al, 1996).…”
Section: Introductionmentioning
confidence: 99%